2018
DOI: 10.1001/jamaneurol.2018.0463
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic Meningitis Investigated via Metagenomic Next-Generation Sequencing

Abstract: Identifying infectious causes of subacute or chronic meningitis can be challenging. Enhanced, unbiased diagnostic approaches are needed. OBJECTIVE To present a case series of patients with diagnostically challenging subacute or chronic meningitis using metagenomic next-generation sequencing (mNGS) of cerebrospinal fluid (CSF) supported by a statistical framework generated from mNGS of control samples from the environment and from patients who were noninfectious. DESIGN, SETTING, AND PARTICIPANTS In this case s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
237
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 242 publications
(250 citation statements)
references
References 31 publications
(68 reference statements)
3
237
0
2
Order By: Relevance
“…24 The diagnosis of NCC was confirmed with a clinical CSF cestode antigen assay and serology, which previously had not been performed. After computational filtering, there were 67,334 pairs of high-quality, nonhuman, and nonredundant sequences.…”
Section: Research Csf Metagenomic Sequencingmentioning
confidence: 92%
See 2 more Smart Citations
“…24 The diagnosis of NCC was confirmed with a clinical CSF cestode antigen assay and serology, which previously had not been performed. After computational filtering, there were 67,334 pairs of high-quality, nonhuman, and nonredundant sequences.…”
Section: Research Csf Metagenomic Sequencingmentioning
confidence: 92%
“…Many of these conditions can cause chronic meningitis with a relapsing component, and broad diagnostic tests, such as cultures, may detect some (but not all) of these pathogens. 15,22,24,25 However, this patient was not known to be immunocompromised or to have engaged in intravenous drug use, making fungal meningitis less likely. Anatomically related cranial and radicular nerve roots become edematous and hyperemic before being entrapped and clumped together 164 Volume 85, No.…”
Section: Infectiousmentioning
confidence: 97%
See 1 more Smart Citation
“…However, these cultures require prolonged incubation periods before confirmation of a negative result can be made, and some results may be negative in infected patients who received previous anti‐microbial therapy . Accordingly, securing a final diagnosis can take weeks or months of testing, and many cases will remain unsolved, necessitating empirical treatment approaches that may be ineffective or even harmful to the patient …”
Section: Introductionmentioning
confidence: 99%
“…Traditional testing methods such as PCR, serological typing, bacterial culture and antibody detection, are regarded as the "gold standard" and widely used in ARI diagnosis 6,7 . However, despite an ongoing effort to include multiple pathogens in a single assay 8,9 , it remains difficult to simultaneously identify all potential ARI pathogens and capture new or uncommon respiratory pathogens 10 .Metagenomic next-generation sequencing (mNGS) is an unbiased way of discovering a broad range of infectious agents [11][12][13] , and has been recently introduced into clinical research to investigate the microbial cause of unusual disease cases 14 , perform broad-scale surveys for pathogens in undiagnosed diseases 15,16 , and understand the role of opportunistic infections 17,18 . For example, a study of severe pneumonia revealed that mNGS is both efficient and reliable 19,20 .…”
mentioning
confidence: 99%